Osnovanje, razvoj in delovanje Slovenskega verskega središča svetih bratov Cirila in Metoda v Melbournu in Avstraliji - Koderman, Miha (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
Intense emigration of Slovenes to Australia started after the World War One and reached climax in the 1950s and 1960s. According to appraisals of several Slovene emigrant organizations, the number of Slovenians settled in Australia in the 1980s must have been about 25.000 - 30.000. Despite the fact that Slovenians in Australia are the fourth largest non-European Slovene emigrant community (after the Slovene emigrant communities in the USA, Canada and Argentina), they have so far been subject to very few research studies.The present article is therefore a humble contribution to the research of Slovene emigration in Australia, which - considering the extent of its activities - would require several vast research studies. The few female authors having dealt with this community are Čebulj Sajko, Birsa, Mikačič and Mikola. The most numerous Slovene community in Australia is in the Federal State of Victoria; the there settled Slovene emigrants are organized in six ethnic associations, sharing a common religious center. The article discusses one of the major and first organizations of the Slovene emigration - the religious center of the Holy Brothers Ciril and Metod in Melbourne. It brings a survey of the most important turning points and events in its history.Soon after its establishment it surpassed the limits of a Catholic Franciscan "mission" and significantly contributed to the preservation of the Slovene community's ethnic identity. To this day it remains an integral part of Slovene emigrant life.
Keywords: Australia; Avstralija; slovenski izseljenci; Slovensko versko središče svetih bratov Cirila in Metoda